2019
DOI: 10.3390/nu11040940
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD163-Associated Dietary Patterns and the Risk of Metabolic Syndrome

Abstract: Elevated soluble cluster of differentiation 163 (sCD163) concentrations, a marker of macrophage activation, are associated with obesity. Weight reduction decreases circulating CD163 levels, and changes in sCD163 levels are associated with improved metabolic dysfunction. Currently, the relationship between sCD163 and diet remains unclear. This study investigated dietary patterns associated with sCD163 concentrations and its predictive effect on metabolic syndrome (MetS). Data on anthropometrics, blood biochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In order to include only dietary factors highly associated with disease or health conditions of interest, we excluded dietary factors discovered by PCA or EFA that focused purely on dimension reduction of the multivariate dietary frequency variables. A total number of 19 articles were included in this review [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The flow chart of searching literatures is shown in Figure 1.…”
Section: Strategy To Search Taiwanese Dietary Pattern-related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In order to include only dietary factors highly associated with disease or health conditions of interest, we excluded dietary factors discovered by PCA or EFA that focused purely on dimension reduction of the multivariate dietary frequency variables. A total number of 19 articles were included in this review [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The flow chart of searching literatures is shown in Figure 1.…”
Section: Strategy To Search Taiwanese Dietary Pattern-related Literaturementioning
confidence: 99%
“…No matter what similarities or differences are discovered, they may provide insight into components of diet that work toward better or worse health. In this endeavor, we reviewed data mining-related literature [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] pertaining to Taiwanese dietary patterns and multiple health or disease outcomes and also described the recent Taiwanese dietary content using data collected in the Nutrition and Health Survey in Taiwan from 2017 to 2020 in order to shed light on healthy eating patterns and options in Asians.…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed increased BMI and WHR, dyslipidemia, FSI and IR in patients with RT particularly with the development of CAD and these abnormalities were positively correlated with serum sCD163 levels supporting the link between macrophage activation and metabolic abnormalities. Previous studies showed an association between serum sCD163 concentration and a less favorable metabolic profile as judged by higher BMI, waist circumference, visceral fat [ [40] , [41] , [42] ], glucose homeostasis parameters, insulin [ 43 ], HOMA-IR [ 41 ], TC [ 43 ], LDL-C [ 40 ] and TG and by a lower HDL-C [ 42 ]. Moreover, Hu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hu et al. [ 42 ], found that sCD163 levels independently predicted the risk of metabolic syndrome and central obesity and had positive trends with diabetes, dyslipidemia and non-alcoholic fatty liver disease. During lifestyle intervention, the change in sCD163 was positively associated with changes in BMI, FBG [ 44 ], HOMA-IR [ 22 , 44 ] and cholesterol, and inversely associated with the change in HDL-C [ 22 ] in obese subjects and patients with non-alcoholic fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion of adipose tissue MFs is beyond the scope of this manuscript, but they are extensively reviewed elsewhere [ 154 , 155 , 156 , 157 , 158 ]. MF activation in general is associated with disease severity in clinical NASH [ 159 , 160 , 161 ] and, moreover, correlates with dietary patterns [ 162 ].…”
Section: Macrophages During Gut-liver Axis Disruption In Chronic Liver Diseasementioning
confidence: 99%